FRI0176 ABT-122, A Novel Dual Variable Domain (DVD)-IG™, Targeting TNF and IL-17, Inhibits Peripheral Blood Mononuclear Cell Production of GM-CSF and Decreases Lymphocyte Expression of CXCR4 in Healthy Subjects. (9th June 2015) - Ruzek, M.; Conlon, D.; Mansikka, H.; Padley, R.J.; Cuff, C.
Abstract : Background: TNF and IL-17 contribute to the pathogenesis of several inflammatory disorders and are known to synergistically induce chemokines and cytokines, including chemokine (C-X-C motif) ligands 1 (CXCL1), 5 (CXCL5), and 8 (CXCL8), chemokine (C-C motif) ligand 2 (CCL2), IL-1β, IL-6, G-CSF, and GM-CSF. In addition, the CXCL12 chemokine receptor, CXCR4, is reported to be coordinately regulated by TNF and IL-17. As these factors play a role in the pathogenesis of several autoimmune diseases, greater clinical responses in patients may be possible with dual neutralization of TNF and IL-17. ABT-122 is novel DVD-Ig™ molecule targeting both human TNF and IL-17 cytokines and is currently in clinical trials. Objectives: The aim of this study was to determine the biologic response to ABT-122 in healthy volunteers based on known activities of TNF and/or IL-17 in humans. Methods: Twenty-four healthy subjects were administered a single dose of ABT-122 (1.5 mg/kg subcutaneously) in a Phase I trial. PBMCs were collected prior to ABT-122 administration at baseline and at days 7, 15, 36, and 57 post dosing and cryopreserved. Thawed PBMCs were either analyzed directly by flow cytometry for chemokine receptors CXCR1, CXCR4, and CXCR5, or stimulated with LPS. Supernatants from the LPS cultures were analyzed by multiplex analysis (MAPx, Millipore EMD) for CXCL8, CXCL1, CXCL5, CCL2, IL-1β, IL-6, IL-10, G-CSF, and GM-CSF. Results: A single dose of ABT-122 administered to healthy volunteers resulted in 4-fold lower production of GM-CSF through day 57 compared with baseline from LPS-stimulated PBMCs. CXCR4 expression also decreased on B cells, T cells, and monocytes at day 7 compared with baseline with average reductions of 54%, 41%, and 20%, respectively. Decreases in CXCR4 on B cells persisted to day 15 (24%) and day 36 (18%). As GM-CSF and CXCR4 are reported to be synergistically regulated by IL-17 and TNF, these results suggest dual neutralization by ABT-122. Consistent with known activities of anti-TNF agents in RA patients, there were 2.5-fold elevations in the anti-inflammatory cytokine IL-10 and significant 9-12% increases in CXCR5 expression on T cells following administration of ABT-122. Other chemokine/cytokine responses to LPS stimulation and expression of CXCR1 were unchanged after ABT-122. Conclusions: The changes observed in expression of GM-CSF and CXCR4 in healthy subjects with dual neutralization of TNF and IL-17, demonstrate pharmacodynamic activity of ABT-122 DVD-Ig™ protein consistent with the known combinatorial activities of TNF and IL-17. Notably, the effects of ABT-122 on these analytes were demonstrated in healthy volunteers, thus these changes likely reflect modulation of the in vivo homeostatic activities of TNF and IL-17 in the absence of disease. These data further support the rationale that ABT-122 can be used to evaluate the therapeutic potential of dual IL-17 and TNF blockade in patients with disorders driven by these two cytokines. Acknowledgements: Stacey Orzel and the Phase I Unit, Renee, Heuser, Ping Jiang, Shekmann Wong Disclosure of Interest: M. Ruzek Employee of: AbbVie, D. Conlon Employee of: AbbVie, H. Mansikka Employee of: AbbVie, R. Padley Employee of: AbbVie, C. Cuff Employee of: AbbVie